Transit's downward spiral: Assessing the social-justice implications of ride-hailing platforms and COVID-19 for public transportation in the US. (January 2022) - Monahan, Torin; Lamb, Caroline G.
Abstract: This paper explores the interconnections between ride-hailing platforms and public transit systems in large US cities. Drawing upon qualitative interviews with expert key informants representing city government agencies, industry, community groups, and others, we find that ride-hailing platforms have catalyzed a downward spiral in many public transportation systems: as more people use ride-hailing instead of transit, transit systems receive less revenue and must reduce services to compensate, which makes transit seem even less desirable to would-be riders, leading more people to explore other transit options. Prior to the COVID-19 pandemic, preexisting transit deficiencies, shifting customer expectations, and stigmatization of transit systems and riders each contributed to ride-hailing platforms' successful encroachment upon public transit. The pandemic has fundamentally destabilized both transit systems and ride-hailing alternatives, but it portends an even greater decline in transit as people gravitate to privately owned vehicles and eschew sharing rides with others. Ride-hailing and transit partnerships, such as a Boston-based pilot project to provide paratransit services for people with disabilities, point to possibilities for complementary arrangements moving forward, but they remain constrained by their industry-focused market models. The current downward spiral is particularly concerning because it negatively impacts the most vulnerable and disempowered in society. Highlights: This study explores threats to public transportation by ride-hailing platforms and the COVID-19 pandemic in large US cities. Interviews were conducted with expert key informants representing city government agencies, industry, and community groups. Many public transportation systems are encountering a downward spiral with reduced ridership and loss of fare-based revenue. This downward spiral negatively impacts the most vulnerable and disempowered in society, raising social justice concerns. Corrective ride-hailing and transit partnerships are constrained by industry-focused market models.